The Power of Good: A Leader's Personal Power as a Mediator of the Ethical Leadership-Follower Outcomes Link - Haller, Daniela K.; Fischer, Peter; Frey, Dieter (Frontiers in Psychology, 2018)
The study’s goal was to examine the socially responsible power use in the context of ethical leadership as an explanatory mechanism of the ethical leadership-follower outcomes -link. Drawing on the attachment theory (Bowlby, 1969/1982), we explored a power-based process model, which assumes that a leader’s personal power is an intervening variable in the relationship between ethical leadership and follower outcomes, while incorporating the moderating role of followers’ moral identity in this transformation process. The results of a two-wave field study (N = 235) that surveyed employees and a scenario experiment (N = 169) fully supported the proposed (moderated) mediation models, as personal power mediated the positive relationship between ethical leadership and a broad range of tested follower outcomes (i.e., leader effectiveness, follower extra effort, organizational commitment, job satisfaction, and work engagement), as well as the interactive effects of ethical leadership and follower moral identity on these follower outcomes. Theoretical and practical implications are discussed.